Environmental sanction procedure in Colombia: General aspects and challenges for its enforcement - Amaya Arias, Ángela María (2020)
This article aims to present the environmental sanction procedure in the Colombian legal system, established by Law 1333 of 2009. The first part will give a general description of the procedure and its different elements. The second part will present the main challenges in its application, after 10 years of the entry into force of said procedure.